Pulmonary artery compression by haemorrhage from the aorta simulating pulmonary embolism. Issue 1 (January 1974) - Franklin, D. H.; Jacques, J.
Abstract : Franklin, D. H., and Jacques, J. (1974). Thorax, 29, 142-144. Pulmonary artery compression by haemorrhage from the aorta simulating pulmonary embolism. A case is presented in which pulmonary embolism was simulated by compression of the pulmonary artery by haematoma during an episode of acute bacterial endocarditis occurring 18 months after aortic valve replacement.